Theology and Literature: Rethinking Reader Responsibility
XII, 240 p.
Keywords: By examining theological and literary narratives through an engagement with well-known theorists of reading and religion, this collection of essays, international in perspective, brings together varied, refreshing and provocative responses to well-established literary and critical theories.